ترقية الحقوق السياسية للمرأة وتعزيز دورها في الجزائر (El-Wahat Journal for Research and Studies, 2021)
Algerian Women Took Their Place In The Constitution, Based On The Gains And Successes Achieved By Women During The Glorious Liberation Revolution. They Struggled And Resisted Side By Side With Their Brother, The Man, With The Aim Of Freedom And Independence Of The Country. Then, Building A Democratic State With A Social System That Guaranteed Equality For All Algerians And Algerians. Women's Political Rights Are An Essential Element In The Consolidation And Embodiment Of Democracy On The Ground, In Particular By Enhancing Their Access To Popularly Elected Councils At All Levels. Organic Law 12-03, Aimed At Strengthening Its Role In The Construction And Protection Of The Country, It Defines How To Expand Women's Representation In The Elected Councils, In Accordance With Article 31 Bis Of The Constitution 2008. Keywords - Women's Political Rights - Quota System - Constitution2008 - Organic Law 12-03